76.8k views
2 votes
Solve.
6x – 25 = 3(4x + 9) + 14
How do I do this or like just do the steps for me?

User Ymz
by
5.6k points

2 Answers

2 votes

Answer:

I think it is - 11.

Explanation:

6x - 25 = 12x + 27 + 14

6x - 12x = 25 + 27 + 14

- 6x = 52 + 14

- 6x = 66

x = - 11

User MisterManSam
by
6.3k points
5 votes

Answer:

x=-11

Explanation:

6x – 25 = 3(4x + 9) + 14

Distribute

6x – 25 = 12x +27 + 14

Combine like terms

6x – 25 = 12x +41

Subtract 6x from each side

6x -6x-25 = 12x-6x+41

-25 = 6x+41

Subtract 41 from each side

-25-41 = 6x+41-41

-66 = 6x

Divide each side by 6

-66/6= 6x/6

-11=x

User Payedimaunt
by
5.7k points